The Influence of Murotal Therapy on Anxiety and Stress Hospitalization in Preschool Children - Diandini, Reza; Inayah, Iin; Rakhmawati, Windy; Murtiningsih, Murtiningsih (JOSING: Journal of Nursing and Health, 2023)
This study aims to overcome the anxiety and stress of hospitalization in preschool children; hospitalized children apply several interventions, such as creating a child-friendly environment, but no other interventions. This study uses a quantitative approach and uses statistical formulas to help analyze the data and facts obtained. The results of this study were in the form of the proportion of anxiety levels in preschool children before being given intervention in the intervention group; namely, the majority of respondents experienced moderate anxiety, as much as 34.3%, while in the control group, the majority of respondents experienced anxiety. They were experiencing mild anxiety, as much as 45.7%. The percentage of stress levels in preschool children before intervention in the intervention group was that most respondents experienced severe stress, as much as 100%. In the control group, most respondents experienced extreme pressure, as much as 54.3%. The percentage of anxiety levels in preschool children after intervention in the intervention group, namely, most respondents were not as worried as much as 48.6% after the intervention. In the control group, most respondents experienced moderate anxiety, as much as 40%. The percentage of stress levels in preschool children after intervention in the intervention group, namely, most respondents experienced mild stress, as much as 57.1%. In the control group, most respondents experienced severe stress, as much as 54.3%. In conclusion, there is an effect of murotal therapy on anxiety levels in preschoolers, but there is no effect of murotal treatment on stress levels in preschoolers. Keywords: Anxiety, Murotal Therapy, Preschool Children, Stress Hospitalization